1995
DOI: 10.1021/ma00130a010
|View full text |Cite
|
Sign up to set email alerts
|

The Elementary Cellulose Fibril in Picea abies: Comparison of Transmission Electron Microscopy, Small-Angle X-ray Scattering, and Wide-Angle X-ray Scattering Results

Abstract: The wood cell wall is built with elementary cellulose fibrils (ECF) having a uniform thickness of 25 ± 2 A. This was shown by investigating the same samples independently with three different experimental techniques, transmission electron microscopy (TEM), wide-angle X-ray scattering (WAXS), and small-angle X-ray scattering (SAXS). Discrepancies between results from these techniques discussed in many earlier studies did not appear in the present work. In particular, it was shown that the size distribution meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
143
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 8 publications
18
143
3
2
Order By: Relevance
“…X-ray diffraction patterns from wood with very well oriented microfibrils resemble the fiber diffraction pattern from crystalline cellulose Iα and Iβ but are much more diffuse (19,23,39). At such a low level of resolution it is not possible to distinguish the Iα and Iβ forms by crystallographic means (45) and for clarity all reflections are indexed here on the Iβ lattice.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…X-ray diffraction patterns from wood with very well oriented microfibrils resemble the fiber diffraction pattern from crystalline cellulose Iα and Iβ but are much more diffuse (19,23,39). At such a low level of resolution it is not possible to distinguish the Iα and Iβ forms by crystallographic means (45) and for clarity all reflections are indexed here on the Iβ lattice.…”
Section: Resultsmentioning
confidence: 83%
“…X-ray scattering from wood in its native state is dominated by the form function. Jakob, et al (23) succeeded in extracting an interference contribution numerically, but it was small and difficult to characterize. From this observation it may be concluded that either the packing of wood microfibrils is too irregular to diffract strongly (42) or there is insufficient X-ray contrast between the microfibrils and any interstitial material (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray diffraction has previously been used for Arabidopsis samples (Fujita et al, 2011). With x-ray diffraction, information on crystallinity, crystallite size, and orientation of cellulose can be gained with very little sample preparation (Jakob et al, 1995). We analyzed intact stems rather than fractionated cellulose as cellulose crystallinity (Hermans and Weidinger, 1949) and crystallite size (Haase et al, 1976) are sensitive to acid treatments.…”
Section: Mutations In the Ctls Affect Cellulose Fibril Assemblymentioning
confidence: 99%